2016
DOI: 10.5433/1679-0359.2016v37n1p95
|View full text |Cite
|
Sign up to set email alerts
|

Response of soybean and corn to soil mechanical intervention and agricultural gypsum application to the soil surface

Abstract: Agricultural gypsum is considered an important tool in the improvement of soil chemical properties; however, crop responses to its application are contradictory. Studies have shown that the physical effects of soil mechanical intervention is short-lasting and has little impact on grain yield. Therefore, the aim of this study was to investigate corn and soybean response to soil mechanical interventions and to the application of agricultural gypsum to soil surface. The experiment involved cultivation of two crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…This is especially apparent in soils containing little organic matter to bind Al and reduce its activity in the soil solution as a result (Bortoluzzi et al, 2014;Joris et al, 2016). The application of gypsum to soils with a low subsoil Al saturation (<10%) caused a slight decrease in soybean yield (0.3% on average; Figure 6), consistent with the results of Pauletti et al (2014) and Somavilla et al (2016). Based on the critical thresholds for soybean (Al saturation >10% under water-deficient conditions), the probability of this crop responding in a negative manner to gypsum was 40%.…”
Section: (D)supporting
confidence: 80%
See 3 more Smart Citations
“…This is especially apparent in soils containing little organic matter to bind Al and reduce its activity in the soil solution as a result (Bortoluzzi et al, 2014;Joris et al, 2016). The application of gypsum to soils with a low subsoil Al saturation (<10%) caused a slight decrease in soybean yield (0.3% on average; Figure 6), consistent with the results of Pauletti et al (2014) and Somavilla et al (2016). Based on the critical thresholds for soybean (Al saturation >10% under water-deficient conditions), the probability of this crop responding in a negative manner to gypsum was 40%.…”
Section: (D)supporting
confidence: 80%
“…The solid line inside the rectangle represents the median, the dotted line represents the mean, and vertical lines above and below the box extend to the minimum and maximum values, respectively. The mean effect of gypsum application on crop grain yield (Y) is shown above the box plot, and the number of pair observations (n) used to calculate the mean effect is shown at the bottom shown the positive effects of gypsum application on crop grain yield to be stronger under water-deficient conditions (Pauletti et al, 2014;Somavilla et al, 2016;Tiritan et al, 2016). However, water deficiency was present only in 19% of the studies included in this meta-analysis (Figure 1f).…”
Section: Response Of Grain Crops To Gypsummentioning
confidence: 98%
See 2 more Smart Citations
“…The results of research along this line, however, are contrasting and differ largely according to crop, climate, and initial conditions of the cropland. Thus, some authors reported a large increase in crop yield (Dalla Nora and Amado, 2013; Caires et al, 2016), whereas others observed no appreciable change (Vidigal et al, 2014;Somavilla et al, 2016) and still others found that gypsum reduced yields (Fontoura et al, 2012;Pauletti et al, 2014;Somavilla et al, 2016). Although the effects of gypsum on soil chemical properties are well known, the specific conditions for a favorable effect on crop yield and precise recommendations for usage, remain to be established (Caires et al, 2011b;Dalla Nora and Amado, 2013;Vicensi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%